The Qaul Qadim and Qaul Jadid: A Sociological Review of The Evolution of Islamic Law - Rahmi, Yulia Rahmi; Rozi, Syafwan; Helfi, Helfi (Alhurriyah, 2024)
Through an examination of the evolution of Imam Shafi'i's philosophy, this paper investigates the sociological distinctions between Qaul Qadim and Qaul Jadid in Islamic legal theory. Although Qaul Jadid is a modification of his views after he went to Egypt, Qaul Qadim refers to the legal opinions he presented while in Iraq. The purpose of this study is to identify the social, political, and cultural factors that shaped the change in Qaul Qadim to Qaul Jadid philosophy. This study analyzes the text and applies a historical approach as a qualitative technique. The findings indicated that in addition to regional variations, certain social and cultural shifts in Egypt necessitated amendments to the legislation to make it more relevant to the local population. The adaptability and flexibility of Islamic law in reaction to societal circumstances are highlighted by this research. It strengthens the debate on the evolution and dynamics of Islamic legal thinking and confirms the need for contextualization in the implementation of shari'ah law. Therefore, the knowledge of how Islamic law evolves and remains applicable in different social situations is greatly advanced by this study. Furthermore, a deep grasp of Qaul Jadid and Qaul Qadim supports Islamic law practices in addressing the issues of the modern world. It facilitates their guaranteeing the validity and relevance of sharia law in the many modern situations.